A linguistic study of image and language of self-presentation of men on grindr, a gay networking app - Muhammad Fakhrul Aqil Fadzil; Bahiyah Dato’ Hj. Abdul Hamid (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2020)
People have been posting personal advertisements in newspapers to find romantic partners and pen pals ever since the mid-seventeenth century. The ubiquity of today’s systems such as online location-aware dating applications for meeting nearby partners provide novel social opportunities as well as a variety of ways people chose to portray themselves—especially in the LGBTQIA+ community as well as the men who have sex with men community here in Malaysia. Such is the case of Grindr. This paper explores the way Malaysian men in the gay community portray themselves through critical image analysis and discourse analysis based on the users’ profile pictures as well as their ‘About Me’ section on Grindr. 30 Grindr profiles were analysed. The analysis of profiles reveal two categories of men who are members of the gay community on Grindr; one who is looking for a long-term companionship and the other, those who are looking for casual sexual activities i.e., for short-term companionships. This paper sheds light not only on the language of self-presentation of MSM in Malaysia visually and linguistically but it also sheds light on the linguistic behaviour of men in this particular community so that we can understand their needs and reach out to this particularly marginalised community, despite the society’s negative perceptions towards it.